Mapping bauxite indices using Landsat ETM+ imageries constrained with environmental factors in Foumban area (West Cameroon) - Tematio, P.; Songmene, S.M.; Leumbe, O.L.; Nouazi, M.M.; Yemefack, Martin; Fouateu, R.Y. (Elsevier, 2015)
The present study aims at mapping some western Cameroon bauxites combining results of digital processing of satellite data (ETM+ of LandSat) with the geological, structural, mineralogical and geochemical characteristics of the Foumban area. Two categories of encrusted bauxitic surfaces have been identified: (i) discontinuous surfaces covering a total area of 11.13 km2, and (ii) continuous surfaces overlapping 2.41 km2. Field observations portray discontinuous surfaces with 5.5 m thick bauxitic mantle subdivided into 1.5 m thick discontinuous duricrust lying on 4.0 m thick continuous duricrust. The continuous surfaces are 4.1 m thick bauxitic duricrust. Mineralogical studies showed that the Foumban bauxites exhibit 78–86% of gibbsite, 7–22% of goethite and less than 7% of kaolinite. Geochemically, Al is the most abundant element with 45.6–58.7 wt.% of Al2O3; followed by Fe with 12.9–20.1 wt.% of Fe2O3 and Si with 1.0–3.7 wt.% of SiO2. Element mobility stated with enrichment factor (EF) allows differentiating three chemical elements: strongly depleted with EF < 1 (Si, Ca, Mg, K, Na, Cu, Mn, Zn); strictly enriched with EF > 1 (Al, Fe, Cr); and with irregular depletion and enrichment behavior with EF ± 1 (Nb, Sr, V, Zr). Based on mass-transport function (M), elements decrease as follows: Sr > Nb > Cr > Al > Zr > V > Zn > Fe > Cu > Si > Ca > K = Na > Mg > Mn. The Foumban encrusted bauxites are classified as laterite and iron-rich high grade orth-bauxites with 45.6–58.7 wt.% of Al2O3 and 1.0– 3.7 wt.% of SiO2, with bauxite reserves estimated to 75.8 million tons. The mapping approach has shown to be suitable for delineating encrusted bauxitic surfaces within loose laterites in tropical regions.The present study aims at mapping some western Cameroon bauxites combining results of digital processing of satellite data (ETM+ of LandSat) with the geological, structural, mineralogical and geochemical characteristics of the Foumban area. Two categories of encrusted bauxitic surfaces have been identified: (i) discontinuous surfaces covering a total area of 11.13 km2, and (ii) continuous surfaces overlapping 2.41 km2. Field observations portray discontinuous surfaces with 5.5 m thick bauxitic mantle subdivided into 1.5 m thick discontinuous duricrust lying on 4.0 m thick continuous duricrust. The continuous surfaces are 4.1 m thick bauxitic duricrust. Mineralogical studies showed that the Foumban bauxites exhibit 78–86% of gibbsite, 7–22% of goethite and less than 7% of kaolinite. Geochemically, Al is the most abundant element with 45.6–58.7 wt.% of Al2O3; followed by Fe with 12.9–20.1 wt.% of Fe2O3 and Si with 1.0–3.7 wt.% of SiO2. Element mobility stated with enrichment factor (EF) allows differentiating three chemical elements: strongly depleted with EF < 1 (Si, Ca, Mg, K, Na, Cu, Mn, Zn); strictly enriched with EF > 1 (Al, Fe, Cr); and with irregular depletion and enrichment behavior with EF ± 1 (Nb, Sr, V, Zr). Based on mass-transport function (M), elements decrease as follows: Sr > Nb > Cr > Al > Zr > V > Zn > Fe > Cu > Si > Ca > K = Na > Mg > Mn. The Foumban encrusted bauxites are classified as laterite and iron-rich high grade orth-bauxites with 45.6–58.7 wt.% of Al2O3 and 1.0– 3.7 wt.% of SiO2, with bauxite reserves estimated to 75.8 million tons. The mapping approach has shown to be suitable for delineating encrusted bauxitic surfaces within loose laterites in tropical regions.The present study aims at mapping some western Cameroon bauxites combining results of digital processing of satellite data (ETM+ of LandSat) with the geological, structural, mineralogical and geochemical characteristics of the Foumban area. Two categories of encrusted bauxitic surfaces have been identified: (i) discontinuous surfaces covering a total area of 11.13 km2, and (ii) continuous surfaces overlapping 2.41 km2. Field observations portray discontinuous surfaces with 5.5 m thick bauxitic mantle subdivided into 1.5 m thick discontinuous duricrust lying on 4.0 m thick continuous duricrust. The continuous surfaces are 4.1 m thick bauxitic duricrust. Mineralogical studies showed that the Foumban bauxites exhibit 78–86% of gibbsite, 7–22% of goethite and less than 7% of kaolinite. Geochemically, Al is the most abundant element with 45.6–58.7 wt.% of Al2O3; followed by Fe with 12.9–20.1 wt.% of Fe2O3 and Si with 1.0–3.7 wt.% of SiO2. Element mobility stated with enrichment factor (EF) allows differentiating three chemical elements: strongly depleted with EF < 1 (Si, Ca, Mg, K, Na, Cu, Mn, Zn); strictly enriched with EF > 1 (Al, Fe, Cr); and with irregular depletion and enrichment behavior with EF ± 1 (Nb, Sr, V, Zr). Based on mass-transport function (M), elements decrease as follows: Sr > Nb > Cr > Al > Zr > V > Zn > Fe > Cu > Si > Ca > K = Na > Mg > Mn. The Foumban encrusted bauxites are classified as laterite and iron-rich high grade orth-bauxites with 45.6–58.7 wt.% of Al2O3 and 1.0– 3.7 wt.% of SiO2, with bauxite reserves estimated to 75.8 million tons. The mapping approach has shown to be suitable for delineating encrusted bauxitic surfaces within loose laterites in tropical regions.